Eficiencia de la gestión presupuestaria de los Gobiernos Autónomos Descentralizados Parroquiales Rurales del cantón y provincia de Loja - Riofrio Labanda, Viviana Eloisa (2024)
The Decentralized Autonomous Parish Governments (GADP) were established with the primary objective of ensuring autonomy in the planning and execution of investment projects. This autonomy is secured through the acquisition and generation of diverse income sources that facilitate the funding of these projects, aligning with the prevailing regulations in Ecuador. The research specifically concentrated on assessing the efficiency of budget management within the Decentralized Rural Parochial Autonomous Governments (GADPR) of the Loja Canton during the fiscal years 2020, 2021, and 2022. To accomplish this evaluation, a comprehensive mixed methodology was adopted. This involved gathering quantitative analysis of historical data available within each GADPR. The outcomes of this study underscored that the Ministry of Economy and Finance adheres to the budget allocation guidelines outlined in Article 192 of the Organic Code of Territorial Organization (COOTAD). Simultaneously, it became apparent that a significant majority of GADPR rely on over 53 % of the state budget exhibit current income surpassing their expenses, a favourable aspect ensuring compliance with the Annual Operational Plan (POA). In conclusion, it is imperative for all GADPR to formulate and implement self-financing strategies as a means to diminish reliance on state funding. The potential delays in budget allocation pose a risk to the timely execution of projects or works, underscoring the critical need for self-sufficiency to achieve results that are both prompt and efficient.